Applicability of Group Discussion as a Pedagogic Practice in a Classroom Setting in Health Education- A Brief Commentary - Chaudhry, Astha (Indian Journal of Pharmaceutical Education and Research, 2026)
Student centered learning (SCL) has brought a paradigm shift in the concept of teaching and learning process from an “Instruction paradigm” to “Learning paradigm”. Based on the Andragogic principles of ‘self- directed learning’ by Malcolm Knowles1 and Blooms taxonomy,2 SCL focuses on the constructivism as a theory of learning, wherein the learners construct and reconstruct knowledge in order to learn effectively. SCL happens most effectively when the learning happens as a part of an activity. This brings about a qualitative change in the learner with the development of critical thinking abilities and sense of empowerment. It aims to give the student greater responsibility enabling him to think, process, analyses, synthesise, criticise, apply and solve problems.
Keywords: Commentary; Health